STUDI EMPIRIS PENGARUH HARGA MINYAK MENTAH DUNIA DAN VARIABEL MONETER TERHADAP PEREKONOMIAN INDONESIA PERIODE 1996-2018 - Luthfi Fajar Arifah; Muhammad Basorudin; Muhammad Abdul Majid; Mira Choirunnisa; Putri Lydia Eltheofany S (Jurnal Ekonomi-Qu, 2020)
Oil is one of the strategic energies in the economy. The fluctuations will always be a favorite barometer of economists and world leaders. Therefore, this study aims to convert deeper into the world and monetary variables towards the Indonesian economy for the period 1996-2018. This study uses secondary data from the IMF and BPS. Variables are economic growth, oil prices, and interest rates. Perform the analysis carried out, namely descriptive analysis using Images and inferential analysis with Vector Error Correction Mechanism (VECM). The results of this study are common in the context of economic growth. Meanwhile, there is no economic growth. Meanwhile, at that time economic growth was influenced by economic growth in the first quarter, second and third quarter, growth in oil prices in the previous quarter, and economic growth in the previous quarter. The average value of ECT produced is negative and significant.